2021
DOI: 10.1590/1980-57642021dn15-020011
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric study of the Awareness of Age-Related Change (AARC) Short Scale translated to Portuguese, applied to Brazilian older adults

Abstract: ABSTRACT. The concept Awareness of Age-Related Change (AARC) is defined as a person’s awareness that their behavior, level of physical, cognitive and social performance, and ways of experiencing life have changed as a consequence of having grown older, and not because of disease. Objective: A psychometric study investigating evidence of construct validity and internal consistency of the Portuguese version of the AARC Short Scale was carried out. Method: A convenience sample of 387 individuals aged≥60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The initial factor analysis, however, revealed low factor loadings for three items in the ten-item instrument, namely: “I have more freedom to live my days the way I want,” “I feel more dependent on the help of others,” and “I have to limit my activities.” This may be due to the characteristics of the sample, which consisted of working people under 65 years old with a mean age of 41 – other studies using this 10-item scale have had samples with a higher percentage of retirees, and an average age of around 65 ( 6 , 60 , 61 ). We might speculate, for example, that the low loading of the item relating to increased freedom reflects that working age people must go to work to support their family and raise children, leaving little freedom, whereas retirees do not have this restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The initial factor analysis, however, revealed low factor loadings for three items in the ten-item instrument, namely: “I have more freedom to live my days the way I want,” “I feel more dependent on the help of others,” and “I have to limit my activities.” This may be due to the characteristics of the sample, which consisted of working people under 65 years old with a mean age of 41 – other studies using this 10-item scale have had samples with a higher percentage of retirees, and an average age of around 65 ( 6 , 60 , 61 ). We might speculate, for example, that the low loading of the item relating to increased freedom reflects that working age people must go to work to support their family and raise children, leaving little freedom, whereas retirees do not have this restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The AARC-10SF is multidimensional in capturing adults’ self-perceptions of age-related gains and losses across five behavioral domains: Health and physical functioning, cognitive functioning, interpersonal relations, social-cognitive and social-emotional functioning, and lifestyle and engagement (see Supplementary Table 2 for item wording). Evidence for concurrent, discriminant, and predictive validity of the AARC-Gains and AARC-Losses scales has been reported in different countries ( Kaspar et al, 2019 , 2021 , 2022 ; Neri et al, 2021 ; Sabatini, Ukoumunne, et al, 2020 ). Like for the long form of the questionnaire ( Brothers et al, 2019 ), the two-factor solution was confirmed for the AARC-10SF, using confirmatory factor analysis and independent samples ( Kaspar et al, 2019 ; Sabatini, Ukoumunne, et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the two-dimensionality of AARC measurement in terms of AARC-Gains and AARC-Losses, Neri et al (2021) presented evidence of factorial invariance of the gains and losses dimensions in young old (60–69 years) and old–old (70+ years) Brazilians based on split-sample confirmatory and exploratory factor analyses (CFA, EFA). Testad et al (2022) reported the first evidence of a potentially more complex pattern of factor loadings of the two-dimensional scale in an age-diverse (50+) Norwegian sample.…”
Section: The Concept Of Awareness Of Age-related Changementioning
confidence: 99%